Confrontations between good and evil are here to stay - Omer, Spahic (AboutIslam.net, 2019)
Following the New Zealand tragedy, much has been said and written about Islamophobia, hate, racism, extremism, etc. The causes, objectives and modi operandi of the unfortunate phenomena have been dealt with extensively and with different degrees of success by a great many religious leaders, politicians, educators and social activists alike, with New Zealand and its prime minister leading the way. The discourses transcended the boundaries of race, nationality, religion and culture, resulting in myriads of voices coming out together and in unison condemning all manifestations of hate, bigotry, extremism and terrorism, and their protagonists, while at the same time emphatically preaching and propagating their antitheses: love, tolerance, peace and dialogue. However, several questions still must be asked, such as: now what in the wake of such an outpouring of emotions and rhetoric, and what is the next step? Will the world go back to its old ways until something similar, or worse, happens and we then do the same thing again, making thereby in the eyes of Islamophobes and other hate and terror-mongers a mockery of ourselves and the ways we deal with some of the most perilous issues? Or will the world do something genuinely meaningful and enduringly effective, facing head-on and trying to contain the contagious menaces which, it is no exaggeration to say, have brought the whole world to a historic crossroads.